THE TOURISM ELEMENT PRODUCT DEVELOPMENT OF SEMARANG OLD CITY BASED ON ATTRACTIVE URBAN HERITAGE APPROACH - Meytasari, Cinthyaningtyas; Tisnawati, Endah (ARSITEKTURA, 2018)
The Old Town Semarang is a historical asset of the former Dutch East Indies colonial that is rich in tourism and science potential. The Old Town Semarang as a historical tourist attraction, divided into aspects of products, physical environment and the driving force of tourism elements. Each aspect has been possessed by The Old Town Semarang, but needs development in order to realize the Old Town Semarang as study center and attractive urban heritage tourism through the development of heritage products, and supported by elements of driving elements of tourism, such as government, private and community, through product studies and the driving force tourism, so that the Old Town Semarang can play a role in science regional tourism, even national, with the needs, tour / tour guides, and community, against the Old Town Semarang. Although in fact there are several inhibiting factors in realizing the Old City of Semarang as a historical tourist attraction.